1988
DOI: 10.1073/pnas.85.15.5507
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus replication by antisense oligodeoxynucleotides.

Abstract: authors request that the following correction be noted. In both papers, the statement that toxicity studies in mice were performed using compound at a concentration of 640 ,ug/ml is incorrect. In all cases, various concentrations of oligodeoxynucleotides were in a volume of 1 ml of pyrogenfree distilled water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(90 citation statements)
references
References 35 publications
1
88
0
1
Order By: Relevance
“…In earlier reports, we demonstrated that replication of human immunodeficiency virus (HIV) could be inhibited by normal phosphodiester oligodeoxynucleotide sequences complementary to HIV RNA (4,8). However, relatively short half-lives of normal oligonucleotides (9) in serum and in cells due to the presence of nucleases, and possibly the low permeability of these charged molecules into normal cells, limit their potential usefulness in vivo.…”
mentioning
confidence: 99%
“…In earlier reports, we demonstrated that replication of human immunodeficiency virus (HIV) could be inhibited by normal phosphodiester oligodeoxynucleotide sequences complementary to HIV RNA (4,8). However, relatively short half-lives of normal oligonucleotides (9) in serum and in cells due to the presence of nucleases, and possibly the low permeability of these charged molecules into normal cells, limit their potential usefulness in vivo.…”
mentioning
confidence: 99%
“…Major applications of such technologies have been for knockdown of gene expression by targeting mRNA with antisense oligonucleotides (AOs) to either block gene translation or induce mRNA degradation (4). Application of antisense technologies for interference with gene splicing was first established for the correction of the mutated ␤-globin gene.…”
mentioning
confidence: 99%
“…(23,25,26) Anti-sense molecules were shown by several groups to inhibit HIV-1 in vitro when targeted towards critical HIV-1 genes such as tat, rev, and integrase, but the need for large amounts for in vivo studies apart from the problems associated with stability contributed to their failure to enter the clinic. (27) 4. RNA interference (RNAi): A natural way of gene silencing Diseases, for which a foreign gene can be identified as the cause, such as in the case of viral infections, are potentially treatable by blocking its expression that will cripple the causative agent.…”
Section: Newer Approaches To Therapymentioning
confidence: 99%